Case report: A novel perspective on the treatment of primary tracheal small cell carcinoma: a patient’s experience with immuno-combined EP therapy and literature review - Chen, Yu; Zhu, Hongbin; Wang, Danping; Ye, Yalan; Gao, Jianrong (Frontiers in Immunology, 2024)
Tracheal small cell carcinoma (SCC) is a rare malignancy, for which the optimal treatment strategy has yet to be determined. Currently, treatment largely aligns with the therapeutic guidelines established for small cell lung cancer, although numerous unresolved issues remain. This paper details a case study of a patient with Stage IIIB primary tracheal SCC, who was treated with an immune-combined etoposide-platinum(EP) regimen. This treatment offers valuable insights into innovative approaches for managing such malignancies.. Furthermore, the study includes a comprehensive literature review to better contextualize the findings. The patient, admitted on May 2, 2023, had been experiencing persistent symptoms of airway discomfort for 15 days. A bronchoscopy performed on May 4 revealed tracheal SCC, classified as T4N2M0, IIIB. Following the CAPSTONE-1 study's methodology, the patient underwent six cycles of PD-L1(adebrelimab) combined with EP therapy, leading to significant relief of symptoms and the eventual disappearance of the tracheal mass.